Research on the atmospheric correction for ZY-3 MUX image - Yang, Lei; Pan, Zhi-Qiang; Fu, Qiao-Yan; Han, Qi-Jin; Sun, Ke; Zhang, Xue-Wen; Wang, Ai-Chun (Guang pu xue yu guang pu fen xi, 2013)
The resolution of the ZY-3 MUX data is 5.8 meter, which is used to the subject classification. It is very difficult to use the dark target method for the atmosphere correction due to the lack of near infrared band in ZY-3 MUX data. The present paper uses the atmospheric correction coefficient look-up table (LUT) constructed by the radiation transmission model 6S based on the aerosol optical depth retrieved from the MODIS data for the atmospheric correction of ZY-3 image. To validate the results, the paper compares the surface spectral curves of the gypsum mine and Gobi and the NDVI values from the corrected and TOA reflectance, the relative error of the atmosphere corrected and the ground-based surface reflectance is less than 6%; the atmospheric correction increases the difference between vegetation NDVI and other features NDVI, highlights vegetation monitoring application ability.